Current Problems of Modern Cardiology: Why Is Hypertension Getting Younger? (Eurasian Medical Research Periodical, 2023)
The review article presents data on the prevalence of arterial hypertension in young people, pathogenetic mechanisms and peculiarities of diagnosis.